Physical and mechanical properties of light red meranti treated with boron preservatives - Lee, Man Djun; Tang, Ridge Wei Cheong; Micheal, Zeno; Miqdad, Khairulmaini; Azmi, Roslan; Ahmad Faidzal, Khodori; Hazim, Sharudin; Lee, Pui San (Korean Society of Wood Science Technology, 2024)
This study investigates the influence of varying concentrations of boric acid (BA) preservative on the physical and mechanical properties of light red meranti (LRM) found in Sarawak. LRM or Shorea leprosula samples were treated with various concentrations of BA via the dip diffusion method using American Society for Testing and Materials (ASTM) standards. The physical property, particularly the retention rate and mechanical properties, bending strength, modulus of elasticity (MOE), tensile and compression strength parallel to grain of impregnated and control samples were tested to determine the effects of BA preservative. The retention rate was found to increase with increasing BA concentration and higher surface area to volume ratio. The mechanical properties in terms of the MOE and tensile strength parallel to grain were found to be greater than those of the control samples, whereas the bending strength and tensile strength parallel to grain were lower. Amongst the results, only the retention rate and MOE showed significant interaction effects at 5% level of significance between all factors tested (samples size and BA concentration for retention rate and BA concentration for MOE).